Skin delivery of 5-fluorouracil via ethosomes using microwave as skin permeation enhancement technique / Nauman Rahim Khan - Rahim Khan, Nauman (2016)
This project focused on formulation and investigation of interplay effects of ethosomes, ethanol and microwave for enhanced skin drug retention with minimal systemic absorption. The microwave was used to modify the skin barrier properties to enhance ethosomes and/or drug penetration/and drug retention which is detrimental to treat local malignant melanoma and to enhance patient compliance. Ethosomes are known to fuse with skin to enable local drug retention. Pre-treatment of skin with microwave and applying liquified medicine is deemed to “cement” the skin thereby raising skin drug deposition. 5-fluorouracil loaded ethosomes were prepared and subjected physicochemical characterization.